Prenatal Diagnosis and Termination of Pregnancy for Alobar Holoprosencephaly with Cyclopia at 18 Weeks: A Case Report - Aryani Aziz; Uqbah Abdul Salam (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Holoprosencephaly is a rare brain malformation caused by the failure of the prosencephalon to divide into separate cerebral hemispheres. Alobar holoprosencephaly, the most severe form, presents with a monoventricle, lack of interhemispheric fissures, and craniofacial abnormalities such as hypotelorism and cyclopia. Early diagnosis and counseling are crucial for informed decision-making. This case highlights the ethical and diagnostic challenges involved in managing lethal fetal malformation. Case Report: A 32-year-old pregnant woman at 18 weeks’ gestation was referred to the fetomaternal clinic with a diagnosis of alobar holoprosencephaly, confirmed by ultrasound. The imaging revealed significant fetal malformations. After counseling, the patient chose to proceed with pregnancy termination. The patient underwent induction of labor without immediate complications. Psychological support and post-procedure counseling regarding the possibility of future pregnancies were provided in this case. Written informed consent was obtained from the patient for publication. Conclusion: This case report describes a 32-year-old female, 18 weeks pregnant, diagnosed with alobar holoprosencephaly via ultrasound, who chose to terminate her pregnancy after being counseled on the prognosis. Alobar holoprosencephaly has poor outcomes. Early ultrasound diagnosis and counseling provided the family with the information needed to make an informed decision about pregnancy termination. Multidisciplinary support, including psychological and counseling, is essential for patients and their families when facing complex clinical decisions. Abstrak Pendahuluan: Holoprosensefali adalah malformasi otak yang langka, disebabkan oleh kegagalan prosensefalon untuk membelah menjadi dua hemisfer otak yang terpisah. Alobar holoprosensefali merupakan bentuk paling berat, ditandai dengan adanya satu ventrikel, tidak adanya fisura interhemisferik, serta kelainan kraniofasial seperti hipotelorisme dan siklopia. Diagnosis dan konseling dini sangat penting untuk pengambilan keputusan yang tepat. Kasus ini menyoroti tantangan etis dan diagnostik dalam menangani malformasi janin yang mematikan.Laporan Kasus: Seorang wanita hamil berusia 32 tahun pada usia kehamilan 18 minggu yang dirujuk ke klinik fetomaternal dengan diagnosis alobar holoprosencephaly, yang dikonfirmasi melalui ultrasonografi. Pemeriksaan pencitraan menunjukkan kelainan janin yang signifikan. Setelah konseling, pasien memutuskan untuk melanjutkan dengan pengakhiran kehamilan. Pasien menjalani induksi persalinan tanpa komplikasi. Dukungan psikologis dan konseling pasca tindakan untuk kemungkinan kehamilan berikutnya diberikan pada kasus ini. Persetujuan tertulis untuk publikasi diperoleh dari pasien.Kesimpulan: Laporan kasus ini mempresentasikan kasus wanita 32 tahun hamil 18 minggu, didiagnosis dengan alobar holoprosencephaly melalui pemeriksaan ultrasonografi, dan memutuskan untuk menghentikan kehamilan setelah mendapatkan konseling mengenai prognosis kondisi tersebut. Alobar holoprosencephaly memiliki prognosis yang buruk. Diagnosis dini melalui ultrasound dan konseling memungkinkan keluarga untuk membuat keputusan yang tepat terkait terminasi kehamilan. Dukungan multidisiplin ilmu termasuk dukungan psikologis dan konseling, sangat penting bagi pasien dan keluarga dalam menghadapi keputusan klinis yang kompleks.